THE DOMOSTROY AS AN EDUCATIONAL NARRATIVE IN THE MEDIEVAL AND MODERN RUSSIAN PEDAGOGICAL PARADIGM - Tilk, Maria (Acta Paedagogica Vilnensia, 2014)
The objective of this paper was to analyze the original texts of Domostroy, the 16th-century Russian set of household rules, to find its core value and obligation areas. The texts are analyzed from the point of view of the history of mentality, the experiences from structural-functional analysis are also considered, and the general educational norms that helped to develop the idea of an archaic Russian perfect human being are emphasized. As a result, this study divides the texts of Domostroy into six core value and key obligation areas as the general education norms: (1) The Religious and Ethical Aspects; (2) The Reflection of the Ritual and Etiquette, (3) Emphasising Gender Roles; (4) The Family Model, (5) The Woman, (6) The Food Table as a Ritual and Etiquette. Although the results and the groupings of the texts are preliminary, they are important for the educators of cultural history, because the influences of the Domostroy in general education norms can still be found in the modern Russian society.
Keywords: education for living; religion and ethics; function of women; ritual; etiquette